"Goals and objectives of the science of drawing" - Ilyosjon Mamatov; Ikromova Mavluda Muhammadjon qizi (Genius Journals, 2025)
This scientific article provides a deep scientific analysis of the goals and objectives of the science of pen drawing based on modern fine art pedagogy, applied art, composition theory, optics, drawing, plasticity and the psychology of visual perception. The main goal of pen drawing in the study was to develop observation, constructive thinking, the ability to analyze and synthesize form, spatial imagination, tone and light-shadow perception, the skills of creating an artistic image, and the factors influencing the development of creative thinking in students through scientifically based criteria. The article extensively covers the educational, practical, artistic and scientific functions of pen drawing based on the theories of art historians such as Leonardo da Vinci, Alberti, Du rer, Arnheim, Gombrich, Itten, Kandinsky, as well as Gestalt psychology, the laws of cognitive perception and the principles of pedagogical didactics. The results of the study confirm that the tasks of the science of drawing are a complex, multi-layered scientific and pedagogical system aimed at transforming the student into a visual thinker who clearly perceives form, texture, color, plasticity and spatial structure
Keywords: drawing; constructive analysis; observation